Departmental regional competitiveness rates in Colombia - Solano-Benavides, Elcira; Alandete-Brochero, Nelson De Jesús (Sociedad y Economía, 2020)
This research aims to analyze the regional departmental competitiveness in relation to economic theories and regional per capita GDP in Colombia. A quantitative methodology of principal component analysis and panel data models is used. Among the main results, seven competitiveness indices related to economic theory were found: that of agglomeration has a high degree of inequality with the other departments; that of centrifugal force is related to the factors of land and mining; the infrastructure has large gaps; that of human capital is the one that presents the least inequality due to the coverage in education in the departments; that of geographic economy also reveals low inequality, showing that transportation costs have decreased in Colombia; the one of institutional economy is the one that presents less inequality between the departments and finally the one of science, technology and innovation shows great levels of inequality.